Development of a dried ice cream mix by vacuum drying - Espina, Agnes A.; Acevedo, Teresita P. (1975)
The development of a dried ice cream mix by vacuum drying entails the preliminary standardization of the percentage composition of the ice cream mix, the vacuum drying operation where various time-temperature combinations were used and a study of storage temperature of the dried ice cream mix. Va ration of the percentage fat and stabilizer-emulsifier was accomplished to enhance both flavor and whipping quality of the mix. The 25% fat and the 1% CMC combination proved best in terms of these parameters. Based on moisture analysis and acceptability tests vacuum drying at 65°F fro 15 minutes was recommended. This drying time-temperature combination yielded a moisture content of 2%. The effect of storage temperature of the dried ice cream mix was studied using TBA values to indicate rancidity development. Samples stored at the 55°C oven showed a more remarkable increase in TBA values as compared to samples stored at 32°C oven. Increase in storage temperature greatly accelerated the onset of rancidity. Further study on the use of refrigeration temperature was recommended.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Ice cream, ices, etc